Properties of recycled polyester-cotton blended melange yarns (Indian Journal of Fibre & Textile Research (IJFTR), 2024)
This investigation aims at studying the important yarn parameters of melange yarns prepared from the recycled polyester (r-PET) and cotton fibres. Twelve melange yarn samples have been spun using normal Indian cotton fibre (Shankar-6) and r- PET by the traditional ring spinning technique. Three different yarn linear densities of 15tex, 20tex and 30tex (rounded to next integer) have been spun from four different blend proportions (100% cotton, 75% cotton/25% r-PET, 50% cotton/50% r-PET and 25% cotton/75% r-PET). Important yarn properties, like tensile strength, breaking elongation, yarn evenness, hairiness, abrasion resistance and imperfections, of these twelve melange yarns are tested and analysed. The yarn hairiness and the imperfections decrease with the increase of r-PET fibre in the yarn regardless of the yarn linear density. But the abrasion resistance, yarn evenness, breaking strength and breaking elongation increase with the addition of recycled polyester fibre in the yarn for all three types of yarn linear densities. These melange yarn properties confirm its suitability for the fabrics for apparels. Hence, the recycled polyester can be used as an alternative fibre to the most used virgin polyester fibres in apparels.